Authority of Local Governments in Emergency Conditions in Banten Province - Hia, Era Era; Effendy, Khasan; Prabowo, Hadi; Maryani, Dedeh (International Journal Labs, 2024)
To accelerate the handling of the COVID-19 pandemic, the government implemented Large-Scale Social Restrictions (PSBB) and the Enforcement of Community Activity Restrictions (PPKM) to reduce community activities to suppress the spread of the virus. However, the implementation of this policy presents challenges, especially related to the authority of the local government in Banten Province and the strategies used in the emergency condition. This research uses McMahon's theory of authority, which divides authority into three categories: expert authority, promise authority, and cooperate authority. Local government strategies are analyzed using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach. This research is qualitative with a descriptive method. Data was obtained through observation triangulation, interviews, and document review, and analyzed using the Miles and Huberman method which included data reduction, data presentation, and conclusion drawn. The results of the study show that the authority of local governments in the conditions of PSBB/PPKM is very limited because they must obtain permission from the Ministry of Health and follow the provisions set by the central government. The strategies implemented include: (1) Strength-Opportunity, by utilizing the support of other parties and increasing public awareness; (2) Weakness-Opportunity, in the form of strengthening policy control through cooperation with the TNI/Polri and cross-sector coordination; (3) Strength-Threat, educating the public and meeting basic needs during PSBB/PPKM; and (4) Weakness-Threat, tightening policies and licensing to increase public compliance. This strategy is designed to optimize the role of local governments in dealing with emergency conditions.